Differences between the IPA Learning Outcomes Learning Module Part with Conventional Learning Class IV in SDN Jodipan Malang - Helda Kusuma Wardani (Universitas Negeri Malang, 2014)
Perbedaan Hasil Pembelajaran IPA antara Pembelajaran Modul Bagian dengan Pembelajaran Konvensional Kelas IV SD Abstract: The aim of this study was to test the effectiveness of learning science a significant difference between the learning modules with conventional learning class section IV in SDN Jodipan Malang and describe the realization of the effectiveness and appeal of learning on learning module and conventional learning section. This quasi-experimental research design was used pre- and post-test design or nonequivalent control group. Testing the hypothesis used t test using SPSS. Conclusions from the results of hypothesis testing is no significant difference between the effectiveness of learning modules with conventional learning section on the topic of the relationship between structure and function of plant roots after the implementation of learning. Minimal realization completeness criteria (KKM) classroom learning module parts is very high. Scores posttes conventional learning classes showed no achievement of KKM. Realization appeal the high part of the learning modules according to the whole class learning module sample parts, and the appeal of high-graded conventional learning. KKM realization is directly proportional to the realization of part of the appeal of the learning module. Key Words: learning outcomes, the learning module parts, conventional learning Abstrak: Tujuan penelitian ini adalah menguji perbedaan signifikan keefektifan pembelajaran IPA antara pembelajaran modul bagian dengan pembelajaran konvensional kelas IV di SDN Jodipan Kota Malang dan mendeskripsikan realisasi keefektifan serta daya tarik pembelajaran pada pembelajaran modul bagian maupun pembelajaran konvensional. Penelitian eksperimen kuasi ini menggunakan rancangan pre- and post-test design atau nonequivalent control group design. Pengujian hipotesis digunakan uji t menggunakan SPSS. Simpulan dari hasil uji hipotesis adalah ada perbedaan signifikan antara  keefektifan pembelajaran modul bagian dengan pembelajaran konvensional pada topik hubungan antara struktur akar tumbuhan dan fungsinya setelah dilaksanakannya pembelajaran. Realisasi Kriteria Ketuntasan Minimal (KKM) kelas pembelajaran modul bagian tergolong sangat tinggi. Skor posttes kelas pembelajaran konvensional menunjukkan tidak tercapainya KKM. Realisasi daya tarik pembelajaran modul bagian tinggi menurut seluruh sampel kelas pembelajaran modul bagian, dan daya tarik pembelajaran konvensional dinilai tinggi. Realisasi KKM berbanding lurus dengan realisasi daya tarik pembelajaran modul bagian.  Kata kunci: hasil pembelajaran, pembelajaran modul bagian, pembelajaran konvensional